2017
DOI: 10.1016/j.spinee.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

An allograft generated from adult stem cells and their secreted products efficiently fuses vertebrae in immunocompromised athymic rats and inhibits local immune responses

Abstract: BACKGROUND CONTEXT Spine pain and the disability associated with it are epidemic in the United States. According to the National Center for Health Statistics, more than 650,000 spinal fusion surgeries are performed annually in the United States, and yet there is a failure rate of 15%–40% when standard methods employing current commercial bone substitutes are used. Autologous bone graft is the gold standard in terms of fusion success, but the morbidity associated with the procedure and the limitations in the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…A). In a previous study, we demonstrated that the ECM scaffold exhibits no inherent healing capacity without supplementation with an appropriate cell source . When compared with untreated hBM, VRE‐BIO treated hBM did not affect fusion frequency (5/5 fused in each case) or the volume of the fusion masses (Fig.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…A). In a previous study, we demonstrated that the ECM scaffold exhibits no inherent healing capacity without supplementation with an appropriate cell source . When compared with untreated hBM, VRE‐BIO treated hBM did not affect fusion frequency (5/5 fused in each case) or the volume of the fusion masses (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…For this purpose, hBM was subjected to VRE‐BIO for 1 hour with 800 nM BIO because these conditions resulted in the most robust upregulation of osteogenic parameters tested. The hBM was then combined with a radiolucent scaffold we developed consisting of porcine gelatin foam with hMSC‐derived extracellular matrix and positioned over decorticated the posterolateral processes of the L4‐L6 vertebrae followed by an 8 week (period of healing ) (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations